A Choice Between Being Conserve or Demolish : First Baptist Church Building Bandung - Shirley Wahadamaputera; Dian Duhita Permata (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT : The grandeur of the old buildings is relics of the Dutch colonial time, which still stands in Bandung city which leads us to the heyday of the city's achievements history. A city that was once proposed to be the capital of the Dutch East Indies to replace Batavia gets the interest of famous Dutch architects to come and work in this city. The results of the architects' innovation, enrich as a real dictionary of the architectural style of the past. Today these buildings have to face the challenges of the age, the inability of the owner to finance the maintenance, being moved to the hand of investors who are not responsible to the value of the past, and the lack of public interest since the modern building is more preferred and lack of government regulation as well.  To get an idea of how a private -controlled building being preserved, a building at Wastukencana 40 Bandung which listed into the 99 historic buildings in the City Center area according to the Spatial Plan Regulations is taken as a case to be studied. This study shows that real action and sympathetic socialisation were needed to preserve a heritage building. Keywords : adaptive reuse, conservation, historic building, process